A entoação no processo de (re)organização da linguagem : um estudo de caso em afasia - Moura, Chirlene Santos da Cunha (2012)
The theme for research has been observed for the intonation in the organization of the speech in patients with aphasia, understood as a change in the linguistic system from brain damage, among other commitments, which makes the aphasic feel it very difficult to convey emotion and meaning by speech, causing social withdrawal. In order to identify prosodic features in the process of (re)organization of language by identifying intonation clues of speech in the oral production by the aphasic subject and the organization of intonation strategies through clues presented in the writing of that subject from the Interactional Theory of Intonation of Brazil (1985), the study focuses on promoting the speech of the aphasic subject by exploring intonation clues through the use of different text genres related to the daily practice of aphasic. For this reason, a study was conducted with an aphasic subject, male, with significant difficulties in writing and speaking skills. We selected ten species with predominant features of speech and ten with predominant features of writing. All the proposed activities on the mode of oral genres were performed by the subject, while only seven activities of the written form were accepted and performed satisfactorily. The results indicated the need of working together both the aspects of verbal and nonverbal multimodal and discursive construction. The intonation clues, both in the oral and in the writing, served as facilitators of the process of organizing language by the aphasic subject. The emphasis of the prominence, especially the emphasis on pretonic syllable, played strong constitutive meaning in interaction. Even the hesitation, which is common in the speech of the aphasic, is considered a strategy for organization of thought, and it is marked by intonation clue related to syntactic organization. Thus, we conclude that in the process of (re)organization of language, intonation plays an important role in the construction of meaning in the interaction and facilitates understanding the statement